Recovery of Indantren from Batik Liquid Waste after Fabric Dying and its Application - Maghfiroh Maghfiroh; Daru Anggara Murty; Hutami Puji Lestari (Indonesian Journal of Chemical Science, 2023)
The remaining dyes have been reused, namely indantren which were wasted after the batik coloring process was finished. This study aims to determine the quality of the color test results, fastness to soap washing, dry rubbing and perspiration (acid and base) of the dyes indantren on fabrics after recovery process using the sedimentation method. The process of recovering indantren dyes is carried out by the method of sedimentation of indantren dyes in the residual waste of the dyeing process. The sediment obtained was dried at 80ºC using an oven to obtain the recovered indantren dye powder and then applied to dye cotton fabrics. The fabric color evaluation stage is carried out to test the aging and fastness of recovered indantren dyes if the dyes are reused in the batik process. The color intensity test was carried out using a UV-PC spectrophotometer, the color fastness test to washing soap and perspiration (acid and base) with the gray scale, and the color fastness test to dry rubbing using the staining scale. The results showed that the three types of recovered indantren dyes used in this study had good quality for reuse in the coloring process. Remaining indantren dyes that can be reused are 32,8% of the mass of indantren used in the initial coloring process. The color fastness test to soap washing, dry rubbing and perspiration of the indantren dyes yielded good scores.